The impact of HMG-CoA reductase inhibitors use on the clinical outcomes in critically ill patients with COVID-19: A multicenter, cohort study - Khalid Al Sulaiman; Khalid Al Sulaiman; Khalid Al Sulaiman; Khalid Al Sulaiman; Ohoud Aljuhani; Ghazwa B. Korayem; Ali F. Altebainawi; Shmeylan Al Harbi; Shmeylan Al Harbi; Shmeylan Al Harbi; Abdulrahman Al Shaya; Abdulrahman Al Shaya; et al. (Frontiers Media S.A., 2022)
BackgroundThe cardiovascular complications of Coronavirus Disease 2019 (COVID-19) may be attributed to the hyperinflammatory state leading to increased mortality in patients with COVID-19. HMG-CoA Reductase Inhibitors (statins) are known to have pleiotropic and anti-inflammatory effects and may have antiviral activity along with their cholesterol-lowering activity. Thus, statin therapy is potentially a potent adjuvant therapy in COVID-19 infection. This study investigated the impact of statin use on the clinical outcome of critically ill patients with COVID-19.MethodsA multicenter, retrospective cohort study of all adult critically ill patients with confirmed COVID-19 who were admitted to Intensive Care Units (ICUs) between March 1, 2020, and March 31, 2021. Eligible patients were classified into two groups based on the statin use during ICU stay and were matched with a propensity score based on patient's age and admission APACHE II and SOFA scores. The primary endpoint was in-hospital mortality, while 30 day mortality, ventilator-free days (VFDs) at 30 days, and ICU complications were secondary endpoints.ResultsA total of 1,049 patients were eligible; 502 patients were included after propensity score matching (1:1 ratio). The in-hospital mortality [hazard ratio 0.69 (95% CI 0.54, 0.89), P = 0.004] and 30-day mortality [hazard ratio 0.75 (95% CI 0.58, 0.98), P = 0.03] were significantly lower in patients who received statin therapy on multivariable cox proportional hazards regression analysis. Moreover, patients who received statin therapy had lower odds of hospital-acquired pneumonia [OR 0.48 (95% CI 0.32, 0.69), P < 0.001], lower levels of inflammatory markers on follow-up, and no increased risk of liver injury.ConclusionThe use of statin therapy during ICU stay in critically ill patients with COVID-19 may have a beneficial role and survival benefit with a good safety profile.